Peran Layanan Informasi Dalam Membangun Motivasi Belajar Anak - Arsini, Yenti; Isnaini, Siti R Nur Uli; Ayustin, Syukri Azzahra; Polem, Ayu Muthmainah; Karo-Karo, Imron Azhari (Al-Ittizaan: Jurnal Bimbingan Konseling Islam, 2025)
This research aims to reveal the role of information services in increasing student learning motivation at the Private Madrasah Ibtidaiyah (MIS) in Timbang Lawan Dusun VII Village. Students' learning motivation is influenced by various factors, including parental support which is often inadequate. This research uses descriptive qualitative methods with interviews, observation and literature study as data collection techniques. The qualitative description research provides research findings by describing phenomena that ususally presented as in-depth and detailed narratives. The research results showed 7-10 students in MIS Desa Timbang Lawan having low learning motivation. Information services in guidance and counseling have proven effective in increasing students' understanding of the importance of learning motivation, with 75% of students reporting increased enthusiasm after participating in these services. This research results showed that information services play a role in providing understanding, knowledge, or information needed by students to build and enchance their learning motivation in order to achieve optimal learning outcomes.